Increased Medicare Expenditures for Physicians' Services: What are the Causes? - Melinda J. Beeuwkes Buntin; Jose J. Escarcé; Dana Goldman; Hongjun Kan; Miriam J. Laugesen; Paul Shekelle (SAGE Publishing, 2004)
In light of rising expenditures for physicians' services and the scheduled decreases in the amounts Medicare pays for such services, we identified the sources of change in the volume and intensity of Medicare physicians' services. We found that the per capita volume and intensity of physicians' services used by Medicare beneficiaries increased more than 30% between 1993 and 1998. Our analyses indicated that, at most, half of this increase was due to measurable changes in the demographic composition, places of residence, prevalence of health conditions, and managed care enrollment of beneficiaries. The other half was due to a general increase in the use of care across beneficiary categories.